Pengaruh Thermal Shock dan Komposisi Evaporation Boats, Semen Tahan Api, dan Pasir Silika terhadap Kekuatan Impact dan Foto Makro Lining Refractory - Fajri, Novila Rojabni; Rusiyanto, Rusiyanto; Widodo, Rahmat Doni; Sumbodo, Wirawan; Fitriyana, Deni Fajar (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2021)
The thermal shock behavior of ceramic refractory materials is of particular interest. Refractory materials are submitted to local temperature gradients in service that originate thermal stresses and thermal shock damage to the material. However, thermal shock treatment on the refractory made from evaporation boat waste is not well documented. The purpose of this study is to determine the effect of thermal shock on the strength of refractory with various compositions. In this study, the refractory was made using 100% refractory cement (sample 1). For Sample 2, the refractory was made from a mixture of refactory cement and evaporation boats waste, each of 50%: 50%. Meanwhile, specimen 3 of the refractory is made from a mixture of refactory cement, evaporation boat waste, and silica sand of 40%: 50%: 10%, respectively. The Thermal shock treatment is carried out at a temperature range of 100 – 700oC for each specimen. The effect of thermal shock treatment on the mechanical properties of each refractory specimen was investigated using the impact and macrography test. Temperature variations in thermal shock have different effects on the level of impact strength on impact test specimens. The lowest strength was 0,012297735 J/mm2 at thermal shock 7000C in sample 3, and the highest impact strength was 0,03928934 J/mm2 at 400oC thermal shock temperature in sample 2. The macrographic examination shows the higher the thermal shock temperature, the greater the fracture produced when the impact test is carried out. This is because the hardness of the refractory material increases.